(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
When Amir Sayyid Abdulahad Khan came to power, the economy in Bukhara collapsed, the emirate was dependent on Russia on the political front, and cultural life also declined. The situation in the country of Bukhara was very difficult. On top of that, the greed and bribery of the officials and the oppression of the common people increased. Even some governors and governors in the territory of the Emirate did not want to obey the central authority in Bukhara, but tried to be "independent" in their own way and started a separatist policy.